p
m−2
(λ) = (λ − 1 + ix)(λ − 1 − ix)(v
1
− λ)(v
2
− λ) . . . (v
m−2
− λ)+
v
1
y
2
1
(1 − λ)(v
2
− λ) . . . (v
m−2
− λ)+
v
2
y
2
2
(1 − λ)(v
1
− λ)(v
3
− λ) . . . (v
m−2
− λ)+
. . . + v
m−2
y
2
m−2
(1 − λ)(v
1
− λ) . . . (v
m−3
− λ).
p
0
(λ) = (λ −1 + ix)(λ −1 −ix)(v
1
−λ)(v
2
−λ) . . . (v
m−2
−λ)
p
m−2
(λ) = p
0
+ δ
δ = v
1
y
2
1
(1 − λ)(v
2
− λ) . . . (v
m−2
− λ)+
v
2
y
2
2
(1 − λ)(v
1
− λ)(v
3
− λ) . . . (v
m−2
− λ)+
. . . + v
m−2
y
2
m−2
(1 − λ)(v
1
− λ) . . . (v
m−3
− λ).
p
m−2
p
0
(λ) δ p
0
(λ) λ
1
= 1 −ix, λ
2
=
1 + ix, λ
3
= v
1
, . . . , λ
m
= v
m−2
p
m−2
˜
λ
1
,
˜
λ
2
, . . . ,
˜
λ
m
λ
j
˜
λ
j
δ
λ
1,2
|λ
1
− λ
2
| = o(|v
j
− λ
1
|) |λ
1
− λ
2
| δ
2
p
q A = λ−v = Ω(d)
λ
1
λ
2
|λ
1
−λ
2
| q
q = γ(v
1
−λ) ···(v
n−2
−λ) σ = |λ
1
−
˜
λ
1
|+ |λ
2
−
˜
λ
2
|
σ = O(δ/q
0
) =
m−2
P
j=1
v
j
y
2
j
(1−λ)
γ(v
j
−λ)
v
j
− λ = O(d
j
) 1 − λ = O(γ)
σ = O(
1
d
P
j≥3
l
j
N
) o(γ)
P
j≥3
l
j
= o(d
√
Nl
2
)
˜
λ
1,2
= 1 + −ix + o(γ)
˜
λ
3
= v + o(γ)
˜
λ
1,2
= 1 + −ix + o(γ)
λ = 1 − ix + o(γ) ¯a = (a, b, w
1
, . . . , w
m−2
)
T
¯a (G − λE)¯a =
¯
0
ix −x −y
1
v
1
. . . −y
m−2
v
m−2
x ix 0 . . . 0
y
1
0 v
1
− 1 + ix . . . 0
. . . . . . . . . . . . . . .
y
m−2
0 0 . . . v
m−2
− 1 + ix
a
b
w
1
. . .
w
m−2
=
o(γ)
o(γ)
o(γ)
. . .
o(γ)
.
ixa −xb −y
1
v
1
w
1
−. . . −y
m−2
v
m−2
w
m−2
= o(γ)
xa +ixb = o(γ)
y
1
a +(v
1
− 1 + ix)w
1
= o(γ)
. . . . . . . . . . . . . . . . . .
y
m−2
a +(v
m−2
− 1 + ix)w
m−2
= o(γ)